TEX14 Interacts with CEP55 To Block Cell Abscission - Iwamori, Tokuko (American Society for Microbiology (ASM), 2010)
In somatic cells, abscission, the physical separation of daughter cells at the completion of cytokinesis, requires CEP55, ALIX, and TSG101. In contrast, cytokinesis is arrested prior to abscission in differentiating male germ cells that are interconnected by TEX14-positive intercellular bridges. We have previously shown that targeted deletion of TEX14 disrupts intercellular bridges in all germ cells and causes male sterility. Although these findings demonstrate that intercellular bridges are essential for spermatogenesis, it remains to be shown how TEX14 and other proteins come together to prevent abscission and form stable intercellular bridges. Using a biochemical enrichment of male germ cell intercellular bridges, we identified additional bridge proteins, including CEP55. Although CEP55 is highly expressed in testes at the RNA level, there is no report of the presence of CEP55 in germ cells. We show here that CEP55 becomes a stable component of the intercellular bridge and that an evolutionarily conserved GPPX3Y motif of TEX14 binds strongly to CEP55 to block similar GPPX3Y motifs of ALIX and TSG101 from interacting and localizing to the midbody. Thus, TEX14 prevents the completion of cytokinesis by altering the destiny of CEP55 from a nidus for abscission to an integral component of the intercellular bridge.